2014
DOI: 10.1155/2014/920940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Anomalies: A Community-Based Study in the Northwest of Iran

Abstract: Background. Congenital anomalies are responsible for a remarkable proportion of mortality and morbidity in newborns. The aim of this study was to document the epidemiological features of congenital anomalies in rural areas, northwest of Iran. Method. The study population included live births born between 2004 and 2012 in rural areas of Tabriz district. All health records of the children under 8 years were assessed retrospectively. Results. Of 22500 live births, 254 cases were identified with a primary diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 4 publications
4
17
1
Order By: Relevance
“…The prevalence of birth defects in the present study is 0.58%, which is comparable to other studies in Nepal, Iraq and Iran which reported an incidence of 0.69% and 0.36% [18][19][20]. Our study showed that Musculoskeletal System to be most commonly affected, presenting as cleft lip, cleft palate and club feet which is in line with studies reported from Egypt and India [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of birth defects in the present study is 0.58%, which is comparable to other studies in Nepal, Iraq and Iran which reported an incidence of 0.69% and 0.36% [18][19][20]. Our study showed that Musculoskeletal System to be most commonly affected, presenting as cleft lip, cleft palate and club feet which is in line with studies reported from Egypt and India [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…A study from Iran done about the same period with the current study (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) however reported a similar incidence (11.2/1000 births). 13 There was an increase in the yearly incidence during the study period with the incidence for the year 2014 being over 5 times that of 2007. The reason for this may be the problems of urbanisation such as exposure to environmental pollution and modernisation including exposure to radiation from electronic gadget such as mobile phones and computers with its attendant effects on the populace.…”
Section: Discussionmentioning
confidence: 89%
“…[8][9][10] Differently, other studies report higher frequency of CAs of the cardiovascular system. 5,[11][12][13] On the other hand, the higher frequency of CNS has been reported in several studies in Iran, 14 Japan, 15 Pakistan, 16,17 China, 18 Nigeria, 19 Tanzania, 20 and India. [8][9][10] The etiology of CNS anomalies is multifactor and involves complex interactions between genetic and environmental factors, constituting one of the most common congenital defects.…”
Section: Discussionmentioning
confidence: 99%